Reflexion und Einfühlung - Höner, Julia; Bell-Jones, Gareth; von Girsewald, Annabelle; Müller, Vanessa Joan; Vogel, Felix; Zakaitis, Jonas; KAI 10 - Raum für Kunst der Arthena Foundation, Düsseldorf (Bielefeld ; : Kerber Verlag, 2012)
Czech, Natalie ; Hopf, Alexandra ; Plender, Olivia ; Prouvost, Laure ; Nashashibi, Rosalind ; Skaer, Lucy ; Ullrich, Jens
Kai 10, Raum für Kunst, Arthena Foundation, Düsseldorf, 21. Januar bis 31. März 2012
kunstcatalogus